Karakteristik Beton Normal Substitusi Agregat Halus Bottom Ash Pada Perendaman Asam Sulfat - Iksal Lagalung; Jonie Tanijaya; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This study conducted a feasibility test for bottom ash as a concrete construction material. In this study, the percentage of fine aggregate bottom ash substitution of 0%, 25%, 35% can be used for concrete mixtures with pH-4 sulfuric acid soaking. With the test object used measuring 15 cm x 30 cm and 60 cm x 15 cm x 15 cm as many as 45 samples, using the American Concrete Institute (ACI) method. The test is a compressive strength test. tensile strength and flexural strength of concrete with a design quality of 30 MPa. At the age of 28 days, the compressive strength values were 32.727 Mpa, 33.859 Mpa, 36.782 Mpa. Concrete with substitution of bottom ash as fine aggregate with variations of 0%, 25% and 35% has increased strength as the percentage of bottom ash substitution increases where the higher the percentage of bottom ash substitution, the higher the strength of the concrete, so it can be said that the percentage of bottom ash substitution is directly proportional with concrete strength.